Atherosclerotic Carotid Plaque Composition and Incident Stroke and Coronary Events - Bos, Daniel; Arshi, Banafsheh; van den Bouwhuijsen, Quirijn J A; Ikram, M Kamran; Selwaness, Mariana; Vernooij, Meike W; Kavousi, Maryam; van der Lugt, Aad (Journal of the American College of Cardiology, 2021)
Increasing evidence suggests that atherosclerotic plaque composition rather than plaque size is linked to ischemic cardiovascular events, yet largescale population-based data in asymptomatic individuals remain scarce. This study sought to investigate carotid plaque composition in relation to incident stroke and coronary heart disease (CHD) in a population-based setting. Between 2007 and 2012, 1,349 persons (mean age 72 years, 49.5% women) from the population-based Rotterdam Study who were free from a history of stroke or CHD, in whom carotid ultrasonography showed subclinical atherosclerosis, and who underwent high-resolution magnetic resonance imaging of the carotid arteries to assess plaque characteristics. These included the presence of specific plaque components (intraplaque hemorrhage [IPH], lipid-rich necrotic core, and calcification), and measures of plaque size (maximum plaque thickness and presence of stenosis of more than 30%). Individuals were continuously followed for the occurrence of stroke or CHD until January 1, 2015. The authors used Cox regression models to assess the association of the plaque characteristics with the incidence of stroke and CHD, with adjustments for age, sex, and cardiovascular risk factors. During a median of 5.1 years' follow-up for stroke and 4.8 years for CHD, 51 individuals had a stroke and 83 developed CHD. Independent of maximum plaque thickness and cardiovascular risk factors, the presence of IPH was associated with incident stroke and CHD (fully adjusted hazard ratio: 2.42 [95% confidence interval: 1.30 to 4.50], and 1.95 [95% confidence interval: 1.20 to 3.14]). Presence of a lipid-rich necrotic core and calcification were not associated with stroke or CHD. The presence of IPH in the carotid atherosclerotic plaque is an independent risk factor for stroke and CHD. These findings indicate the promise of IPH as a marker of plaque vulnerability in healthy persons with subclinical atherosclerosis.